An Analysis of Obstacles Faced by English Teacher and Students during Online Learning at SMA N 11 Solok Selatan - Uswatun Nisa; Carbiriena Solusia (Journal of English Language Teaching, 2022)
This study aims to describe the obstacles experienced by teachers and students towards online English teaching and learning activities during the Covid-19 pandemic at SMA Negeri 11 Solok Selatan. In this study, the researcher used a descriptive qualitative technique. In obtaining data, researchers used questionnaires and questionnaires. In this study, questionnaires were given to teachers and students in the form of printouts, while interviews were conducted online via WhatsApp to obtain more information from respondents. The sample used was 1 English teacher and 19 students in class XI and XI at SMAN 11 Solok Selatan. Each teacher is given 15 questions and students 30 questions. The results of the research show that teachers face several obstacles in online learning, such as the lack of mastery of technology so it is difficult to create teaching methods that are easily understood by students. In addition, the most dominant obstacle is the internet network which often experiences disturbances. In addition, most students also face almost the same obstacles regarding a bad internet network, making it difficult to take part in learning English online. however, teachers and students can face some of these obstacles in online learning in their way.